THE EFFECTIVENESS OF SONG AND MUSIC-BASED ACTIVITIES IN TEACHING ENGLISH TO PRESCHOOL CHILDREN - Choriyeva Xurmo (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
ABSTRACT: This article explores the effectiveness of song and music-based activities in teaching English to preschool children. It examines how incorporating songs, rhymes, and musical games enhances vocabulary acquisition, listening comprehension, pronunciation, and oral communication skills. Emphasis is placed on age-appropriate design, interactive participation, and combining music with play-based learning strategies. The findings provide practical recommendations for educators to implement music-based activities effectively, fostering motivation, cognitive development, and early foreign language proficiency in young learners.